2018
DOI: 10.1002/jcb.28017
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of miR‐125b predicts poor response to therapy in pediatric acute lymphoblastic leukemia

Abstract: Background Acute lymphoblastic leukemia (ALL) is the most well‐known sort of leukemia in children. In spite of favorable survival rates, some patients relapse and achieve a poor outcome. Methods We analyzed miR‐125b and Bcl‐2 expressions in pediatric patients with ALL and evaluated their clinical utility as molecular markers for the prediction of disease outcomes. Results Downregulation of miR‐125b and increased Bcl‐2 expression levels in pediatric patients with ALL were associated with poor prognosis at diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“…Instead, most previous data focus on the application of miR‐125a and miR‐125b in predicting prognosis in cancers. For instance, reduced miR‐125a level associates with poor survival in hepatocellular carcinoma patients; downregulation of miR‐125b predicts poor response to therapy and short leukemia‐free survival and overall survival in pediatric acute lymphoblastic leukemia patients . In this present study, we found that miR‐125b but not miR‐125a was decreased in survivors compared with non‐survivors, and it was an independent factor predicting higher risk of mortality in sepsis patients.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Instead, most previous data focus on the application of miR‐125a and miR‐125b in predicting prognosis in cancers. For instance, reduced miR‐125a level associates with poor survival in hepatocellular carcinoma patients; downregulation of miR‐125b predicts poor response to therapy and short leukemia‐free survival and overall survival in pediatric acute lymphoblastic leukemia patients . In this present study, we found that miR‐125b but not miR‐125a was decreased in survivors compared with non‐survivors, and it was an independent factor predicting higher risk of mortality in sepsis patients.…”
Section: Discussionsupporting
confidence: 50%
“…The possible explanations were that miR-125b promoted inflammation and organ dysfunction (or failures) via various ways as aforementioned studies, [14][15][16] downregulation of miR-125b predicts poor response to therapy and short leukemia-free survival and overall survival in pediatric acute lymphoblastic leukemia patients. 20 In this present study, we found that miR-125b but not miR-125a was decreased in survivors compared with non-survivors, and it was an independent factor predicting higher risk of mortality in sepsis patients. These might be due to that miR-125b closely positively correlated with disease severity and inflammation, which resulted in worse outcomes in sepsis patients;…”
Section: Ta B L E 2 Correlation Of Mir-125a/b Relative Expression Witsupporting
confidence: 47%
“…It has been found that this process is mediated through many mechanisms like interferon signaling–mediated hematopoietic stem cell proliferation . Activation of TLR4 with activation of MyD88 signaling results in enhanced myeloid differentiation nuclear factor‐κB (NF‐κB) signaling pathway . The overexpression of miR‐155 initiates a myeloproliferative disorder.…”
Section: Discussionmentioning
confidence: 99%
“…2 Activation of TLR4 with activation of MyD88 signaling results in enhanced myeloid differentiation 3 nuclear factor-κB (NF-κB) signaling pathway. 3,24,25 The overexpression of miR-155 initiates a myeloproliferative disorder. Increasing research points to NF-κB activation in human AML CD34+ cells and many other myeloid malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Several latest research has recognized the aberrant expression of HOTAIR in a number of most cancers types, including breast, gastric, pancreatic, cervical, colorectal and lung cancer, and a higher expression level of HOTAIR has been correlated with high tumor burden and cancer progression, Thereby, knockdown of HOTAIR is able to inhibit the malignant invasion and proliferation and inducing cells apoptosis, consequently indicating that HOTAIR might also characteristic inside the modulation of cancer development [8][9][10][11][12][13][14][15][16]. Presents proof in their look at for the primary time that HOTAIR can also act as an oncogenic gene in AML, and that it could constitute a capability biomarker of bad prognosis and an ability therapeutic goal for AML intervention [5,15]. However, the right molecular mechanisms in the back of the involvement of HOTAIR in AML require similarly investigation [16].…”
Section: Introductionmentioning
confidence: 99%